2018
DOI: 10.1002/cepa.704
|View full text |Cite
|
Sign up to set email alerts
|

Geodatabases to improve geotechnical design and modelling

Abstract: Geotechnical designers and modellers must capture and quantify the variability of key soil properties to make engineering decisions. There is a long history in geotechnical engineering of assembling large databases of past soil tests. This paper shows the use of geotechnical databases in two contexts: (a) slope stability modelling in the Eastern Caribbean and (b) settlement response of bored piles in London Clay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Method 3 -Elastoplastic "t-z" analysis using a power-law nonlinear soil model A linear elastic perfectly-plastic soil model is a relatively crude approximation of the constitutive behavior of soils, neglecting any nonlinear elastic behavior and plastic behavior such as strain softening. Modelling soil nonlinearity rigorously requires numerical analysis, however, Vardanega et al (2012aVardanega et al ( , 2018 proposed a simple analytical method based on mobilised stress design principles that is suitable for hand calculation and can be applied here. The constitutive relationship in Eq.…”
Section: Methods 1 -Linear Elasticmentioning
confidence: 99%
“…Method 3 -Elastoplastic "t-z" analysis using a power-law nonlinear soil model A linear elastic perfectly-plastic soil model is a relatively crude approximation of the constitutive behavior of soils, neglecting any nonlinear elastic behavior and plastic behavior such as strain softening. Modelling soil nonlinearity rigorously requires numerical analysis, however, Vardanega et al (2012aVardanega et al ( , 2018 proposed a simple analytical method based on mobilised stress design principles that is suitable for hand calculation and can be applied here. The constitutive relationship in Eq.…”
Section: Methods 1 -Linear Elasticmentioning
confidence: 99%
“…Equation 4 was found to have an R 2 = 0.56 for n = 47 with p < 0.001. Vardanega et al (2018) found that when ϕ' peak was regressed against liquidity index for the SL database a R 2 of 0.43 was obtained.…”
Section: Geotechnical Correlationsmentioning
confidence: 97%
“…(i) Based on preliminary work by Shepheard et al (2018b) and Vardanega et al (2018), to investigate whether significant soil property correlations can be derived to link soil friction angle to basic soil parameters for the Saint Lucia database (hereafter referred to as the 'SL database');…”
Section: Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2), an investigation is prompted into an estimation expression where the parameters are combined, i.e., the liquidity index (LI). Studying the linear formulation, the use of LI as a sole predictor for ϕ' peak gives a lower coefficient of determination of 0.43 (see Vardanega et al 2018 for the scatter-plot). Therefore, the value in weighting the variables separately (as shown in Eq.…”
Section: Multiple Linear Regression Analysismentioning
confidence: 99%